New ultrahigh-resolution picture of Earth's gravity field - Hirt, Christian; Claessens, Sten; Fecher, T.; Kuhn, Michael; Pail, R.; Rexer, Moritz (American Geophysical Union, 2013)
We provide an unprecedented ultrahigh resolution picture of Earth’s gravity over all continents and numerous islands within ±60° latitude. This is achieved through augmentation of new satellite and terrestrial gravity with topography data and use of massive parallel computation techniques, delivering local detail at ~200 m spatial resolution. As such, our work is the first-of-its-kind to model gravity at unprecedented fine scales yet with near-global coverage. The new picture of Earth’s gravity encompasses a suite of gridded estimates of gravity accelerations, radial and horizontal field components, and quasi-geoid heights at over 3 billion points covering 80% of Earth’s land masses. We identify new candidate locations of extreme gravity signals, suggesting that the Committee on Data for Science and Technology standard for peak-to-peak variations in free-fall gravity is too low by about 40%. The new models are beneficial for a wide range of scientific and engineering applications and freely available to the public.